2003
DOI: 10.1093/cercor/13.9.994
|View full text |Cite
|
Sign up to set email alerts
|

Dominance for Vestibular Cortical Function in the Non-dominant Hemisphere

Abstract: The aim of this (15)O-labelled H(2)O bolus positron emission tomography (PET) study was to analyse the hemispheric dominance of the vestibular cortical system. Therefore, the differential effects of caloric vestibular stimulation (right or left ear irrigation with warm water at 44 degrees C) on cortical and subcortical activation were studied in 12 right-handed and 12 left-handed healthy volunteers. Caloric irrigation induces a direction-specific sensation of rotation and nystagmus. Significant regional cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
397
1
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(479 citation statements)
references
References 69 publications
65
397
1
16
Order By: Relevance
“…[14][15][16][17] These data have implicated a widespread distributed network in the frontal and tempo-parietal areas that strongly overlaps with the neural networks found for spatial attention, 18 with a right hemisphere dominance. 19,20 Behavioural observations in patients with posterior parietal cortical lesions provide further support for the suggested overlapping neural networks. Posterior parietal cortical lesions (particularly on the right) typically result in spatial neglect, a disorder of spatial attention.…”
Section: Cortical Processing and The Vormentioning
confidence: 61%
“…[14][15][16][17] These data have implicated a widespread distributed network in the frontal and tempo-parietal areas that strongly overlaps with the neural networks found for spatial attention, 18 with a right hemisphere dominance. 19,20 Behavioural observations in patients with posterior parietal cortical lesions provide further support for the suggested overlapping neural networks. Posterior parietal cortical lesions (particularly on the right) typically result in spatial neglect, a disorder of spatial attention.…”
Section: Cortical Processing and The Vormentioning
confidence: 61%
“…Congruently, epileptic patients with vestibular aurae suffer from lesions surrounding the superior temporal gyrus and the temporoparietal cortex [99,107]. This location has also been confirmed by functional neuroimaging studies in healthy subjects using caloric and galvanic stimulation of the peripheral vestibular system revealing unanimously predominant activations centered on the TPJ and insula [6,19,20,32,39,46,47,50,51,70,72,85,94,95,110,112,118] with activations in the superior temporal gyrus, posterior insula, inferior parietal lobule (angular and supramarginal gyri), and postcentral gyrus. Although many regions surrounding the TPJ/insula have been found activated, opinions concerning the exact location of the human homologue of the PIVC differ (Fig.…”
Section: The Vestibular Cortexmentioning
confidence: 80%
“…In healthy subjects, sense of body ownership and self-attribution of actions are also more specifically related to right posterior insula activity [49,115]. Also, there is an overall right hemispheric dominance for the vestibular cortex [39,46,50,51,112], and the integration of vestibular and proprioceptive cues seems to involve particularly the right TPJ (see Bottini et al [19]). In the case of autoscopic hallucinations, lesion sites are mostly located in right parieto-occipital and temporo-occipital cortex with less involvement of the TPJ [13,15].…”
Section: Linking Abnormal Body Ownership and Embodiment At The Multismentioning
confidence: 98%
See 1 more Smart Citation
“…There is vestibular dominance in the non-dominant hemisphere and stronger activation occurs in the hemisphere ipsilateral to the stimulated ear [23]. A subsequent human PET study on right-handed patients aVected by right-sided vestibular neuritis showed an activation of the primary vestibular cortex (parieto-insular vestibular cortex-PIVC) on the left side, contralateral to the aVected side, and a deactivation of the supposed "secondary" multisensory vestibular cortex areas on the right side, ipsilateral to the aVected ear [12].…”
Section: Discussionmentioning
confidence: 99%